RES and brain targeting stavudine-loaded solid lipid nanoparticles for AIDS therapy - Dandagi, Panchaxari M; Patel, Punit D; Gadad, Anand P; Aravapalli, Anil Kumar (Asian Journal of Pharmaceutics (AJP), 2014)
Cells of the reticuloendothelial system (RES, e.g., macrophages) play an important role in the immunopathogenesis of Acquired Immunodeficiency Syndrome (AIDS). The objective of the present study was to investigate the possibility of specifically targeting antiviral drugs Stavudine to RES (like Liver, Spleen etc.) and brain using solid lipid nanoparticles (SLNs) as colloidal drug carriers. Various lipids like stearic acid, cetyl palmitate, glyceryl behenate and phospholipid in combination have been used and effect of lipid on properties of SLNs has been investigated. The SLNs of Stavudine were prepared by double emulsion solvent evaporation method.The diameter of SLNs was determined and found in range of 175 ± 6.027 to 393 ± 2.309 nm depending on the type of lipid used. Percentage drug entrapment was found to be influenced by the concentration and type of lipid used, which was found in the range of 18.1 to 65.2%. The drug release behavior was studied by dialysis bag method and the release pattern of drug was found to follow Higuchi model. Results of stability evaluation showed a relatively long-term stability after storage at 4°C for 1 month. Stavudine-loaded SLNs were successfully prepared, optimized and effectively targeted to RES and brain. SLNs of Stavudine have been shown to be taken up by brain 11 fold greater as compared to pure Stavudine. This finding is more important since Human Immunodeficiency Syndrome (HIV) infect the central nervous system.